2018
DOI: 10.2116/analsci.18sbp08
|View full text |Cite
|
Sign up to set email alerts
|

Copper Speciation for Natural Water by On-site Sample Treatment/Solid-phase Extraction/Inductively Coupled Plasma Mass Spectrometry

Abstract: Herein, we determined the contents of Cu(I), Cu(II), and hydrophobic Cu in natural water using on-site sample treatment, solid-phase extraction (SPE), and inductively coupled plasma mass spectrometry (ICP-MS) analysis. To prevent Cu species changes in the sampling, filtering and preconditioning steps were performed in a closed system using plastic syringes and a disposable membrane filter. Bathocuproin disulfonate (BCS) and ethylenediaminetetraacetic acid (EDTA) were selected as a Cu(I)-selective complexing ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 22 publications
(21 reference statements)
0
4
0
2
Order By: Relevance
“…Yabutani et al reported on copper speciation, such as Cu(II), Cu(I) and hydrophobic Cu, in natural water using on-site sample treatment, C18 SPE, and ICP-MS analysis. 13 This developed method was applied to estuarine, riverine, and seawater samples.…”
mentioning
confidence: 99%
“…Yabutani et al reported on copper speciation, such as Cu(II), Cu(I) and hydrophobic Cu, in natural water using on-site sample treatment, C18 SPE, and ICP-MS analysis. 13 This developed method was applied to estuarine, riverine, and seawater samples.…”
mentioning
confidence: 99%
“…Yabutani et al reported on "Copper Speciation for Natural Water by On-site Sample Treatment/Solid-phase Extraction/Inductively Coupled Plasma Mass Spectrometry", describing the speciation of Cu(I), Cu(II), and hydrophobic Cu in natural water. 6 Three SPE runs with/ without bathocuproin disulfonate (BCS) and ascorbic acid (AA) were performed to determine the concentration of total Cu and those of individual Cu fractions. The developed method was applied to natural water collected in Tokushima prefecture.…”
mentioning
confidence: 99%
“…The biotic functions and toxicities of metals generally depend on their chemical states and species. 18,19 Thus, both the determination and distribution of metals and species are required for understanding detailed mechanisms and functions related to metallomics. Narukawa et al reported on a method for the determination of methylmercury (Me-Hg) and inorganic mercury (i-Hg) using HPLC-ICP-MS, assisted by alkaline extraction using tetramethyl ammonium hydroxide.…”
mentioning
confidence: 99%